Vasoplegia in patients following ventricular assist device explant and heart transplantation. (March 2022) - Emmanuel, Sam; Pearman, Madeleine; Jansz, Paul; Hayward, Christopher Simon
Background: Vasoplegia has been shown to be associated with increased morbidity and mortality in patients undergoing cardiac surgery. It has been previously stated that low pulsatile states as seen with current left ventricular assist devices (LVADs) may contribute to vasoplegia post LVAD-explant and heart transplant. We sought to examine the literature regarding vasoplegia in the post-operative setting for patients undergoing LVAD explant and heart transplant. Method: A literature review was conducted to firstly define vasoplegia in the setting of LVAD patients, and secondly to better understand the relationship between vasoplegia and LVAD explantation in the postoperative heart transplant patient cohort. A keyword search of 'vasoplegia' OR 'vasoplegic' AND 'transplant' was used. Search engines used were PubMed, Cochrane Library, ClinicalTrials.gov, Ovid, Scopus and grey literature. Results: 17 studies met the selection criteria for review. Three key themes emerged from the literature. Firstly, there is limited consensus regarding the definition of vasoplegia. Secondly, patients with LVADs experienced higher rates of vasoplegia following heart transplant than their counterparts and thirdly, increased cardiopulmonary bypass time was associated with a higher rate of vasoplegia. Conclusion: Vasoplegia is not clearly defined in the literature as it pertains to the LVAD patient cohort. Patients bridged with LVADs appear to have higher rates of vasoplegia, however the aetiology of this is unclear and may be associated with continuous flow physiology or prolonged cardiopulmonary bypass time. A universal definition will aid in risk stratification, early recognition and management.